Using a situation awareness approach to identify differences in the performance profiles of the world`s top two squash players and pheir opponents - Murray, S.; James, N.; Perš, J.; Mandeljc, R.; Vuckovic, G. (Frontiers in Psychology, 2018)
Purpose: The pressure exerted on a squash player is a consequence of the quality of a shot coupled with the ability of the player to return the ball, namely, the coupling of the two players` situation awareness (SA) abilities. SA refers to an awareness of all relevant sources of information, the ability to synthesize this information using domain knowledge and the ability to physically respond to a situation.